Participação social e governança eletrônica: um estudo acerca da percepção de cidadãos eleitores do município de Itabirito/MG - Silva, Filipe Luiz Mendanha (2023)
Since the 20th century, Public Administration has been seeking more effective and transparent management, and governments must present tools that allow interaction between public services and society. Information and Communication Technologies (ICTs) have become one of the most relevant elements for articulating the operational activities of governments, improving the availability of information and social control of fiscal, budgetary, administrative and public administration management acts. It is in this context that electronic governance emerges, covering citizens' actions with the government through electronic means, allowing society to have freedom of expression in government actions, favoring citizen participation and control over the acts carried out by public managers. Therefore, this study has the general objective of evaluating the perception of participation and social control in the face of the use of electronic governance tools and public information dissemination tools available by the municipality of Itabirito/MG as mechanisms for mitigating and preventing corruption in administration. public. To achieve this exploratory objective, the methodology adopted consisted of descriptive, documentary and qualitative research. Regarding technical procedures, this is a case study and it was defined: as the unit of analysis, the Municipality of Itabirito/MG; as a source of evidence documents, archival records and interviews. With regard to data collection: to verify the theoretical trends of electronic governance as a tool for mitigating and preventing corruption, during the months of August to December 2022, document analysis, interviews and an electronic form were carried out through the platform google docs., which showed a low participation of the population in the process of monitoring municipal government actions, a small percentage of contributions incorporated in the participation of voters in public hearings, in the use of the municipal ombudsman's office, as well as in access to means of electronic government of the municipality of Itabirito/MG and also, a didactic insufficiency of these tools, which is why it makes it difficult to combat, prevent and mitigate corruption in municipal public administration. Furthermore, according to the data collected, it was possible to conclude that social participation must be understood in a qualitative way and that the profile of those surveyed does not correspond to the profile of the population of Itabirito/MG.